CELLULAR GENOME IN PATHOGENESIS OF BASIC DISEASES IN HUMANS (ATHEROSCLEROSIS, AUTOIMMUNE DISEASES, CANCER) - V. A. Kozlov (Медицинская иммунология, 2014)
Despite of considerable differences in etiology, pathogenesis, clinical and laboratory, data, and, finally, different clinical features of such diseases as atherosclerosis, autoimmune and allergic diseases, there exists a lot of evidence suggesting that, basically, these disorders have much in common. First of all, it concerns epigenetic regulatory mechanisms of gene expression that show virtually identical patterns of changes, i.e., total hypomethylation and reversible hypermethylation of distinct genes. The events connected with regulation of telomere length are also similar in all the mentioned disorders. In general, this concept draws attention to current needs for urgent development of novel therapeutic approaches for these very common disorders, by means of drugs that would be able to influence some molecular mechanisms, underlying epigenetic regulation of gene expression.